TARI TANDUAK DALAM KEHIDUPAN MASYARAKAT NAGARI LUBUAK TAROK KABUPATEN SIJUNJUNG: SUATU KAJIAN SEMIOTIKA - Auliana Mukhti Maghfirah (Garak Jo Garik : Jurnal Pengkajian dan Penciptaan Seni, 2023)
Tanduak dance is a traditional performing art form that is performed within the royal court, and without this dance, guests are not allowed to enter the kingdom. Over time, the dance has also been performed in community events, under the supervision of the village head. The existence of Tanduak dance is recognized by the local community as the identity of the village and a genuine cultural product of Nagari Lubuak Tarok, carrying special meanings in the lives of its supporting community. These meanings include the four colors of fabric used in the Tanduak props and the twenty-two mirrors, all of which hold significance in the dance. The aim of this research is to explore and understand the meanings embedded in Tanduak dance in Nagari Lubuak Tarok. The research method used is qualitative, collecting data through observation and studying traditional arts, particularly Tanduak dance and its environment, audio and visual documentation, and interviews with artists and the community. This research is analyzed using semiotic theory. In general, this study found the extent to which artists foster solidarity through the use of universal symbols in their artistic activities.